The Effects of Self vs. Group Affirmation and Message Framing on College Students' Vape-Free Campus Policy Support. Issue 11 (19th September 2021) - Jun, Jungmi; Wen, Taylor J.; Wu, Linwan
ABSTRACT: A growing number of American colleges and universities have become vape-free campuses in response to the high e-cigarette use prevalence among young adults. However, little is known about communication or social-psychological factors associated with campus members' support for a tobacco policy prohibiting e-cigarette use on the campus (vape-free policy support). The present study explores the main and interaction effects of affirmation and message framing on the vape-free policy support among college students who vary in their vaping status. We conducted a computer-based experiment with a two (affirmation: self vs. group) by two (message framing: gain vs. loss) by two (vaping status: vapers vs. non-vapers) between-subjects design. Our analysis indicated that self-affirmation is associated with a higher level of vape-free policy support than group-affirmation. The main effects of message framing as well as two-way interactions between framing and affirmation were not statistically significant. A notable finding was the three-way interaction effect among affirmation, framing, and vaping status. For vapers, the level of policy support was the highest when they were self-affirmed and exposed to a gain-framed message. For non-vapers, the level of policy support was the highest when they were self-affirmed and exposed to a loss-framed message. Our findings suggest that colleges may use varied approaches in communicating a vape-free campus policy based on the target students' vaping status, and the group-pride or collective identity appeals may not be effective in promoting such policy.